COMPARATIVE STUDY OF COHERING SUFFIX IN ENGLISH AND INDONESIA - DWI PEBRINA SINAGA (JURNAL ILMIAH SIMANTEK, 2019)
This paper is analyzing morphologically and phonologically the morphology unit especially for the cohering suffix based on the theory of Morphology proposed by Boiij (2012) in his book, The Grammar of Words: An Introduction to Linguistic Morphology, by interfacing between morphology and phonology approach. Cohering suffix is the suffix forms one domain of syllabification with the stem. The cohering suffix chosen in English is -er while in Indonesia is -an in case they have characteristics of being cohering suffix. Due to this research, the writer uses descriptive method with the objective of this research is to compare the cohering suffix in English and in Indonesia. After analyzing the data, it is able to be concluded that cohering suffix in English and in Indonesia has the same character which is starting from a vowel letter; -er in English and -an in Indonesia. However, there is founded a constraint in Indonesia cohering suffix which it does not happen with the stem ends in vowel as English does, like in man.di.an (that -an forms own domain of syllabification).